BOOK REVIEW Books to Change the World: International Publishers at One Hundred: edited by Tony Pecinovsky & Shannon O'Neill, New York: International Publishers, 2024,190 pp. - Huang, Yuan (American Communist History)
The article discusses "Books to Change the World: International Publishers at One Hundred," a compilation that marks the centennial history of International Publishers (IP) and its contributions to Marxist literature and social movements. The volume is structured into two sections: scholarly articles from a centenary seminar and key historical documents, providing insights into IP's role in promoting social justice, women's liberation, and racial equality. While the anthology is praised for its academic rigor and diverse content, it faces criticism for insufficient depth in certain areas, uneven topic coverage, and a limited theoretical framework primarily focused on classical Marxism. Overall, the book serves as a significant resource for scholars studying the intersection of publishing and social change.